2020
DOI: 10.1111/sms.13871
|View full text |Cite
|
Sign up to set email alerts
|

Combination of resistance and aerobic exercise for six months improves bone mass and physical function in HIV infected individuals: A randomized controlled trial

Abstract: To evaluate the effect of combined resistance and aerobic training (RT+AT) on regional bone mineral density (BMD) and physical performance in people living with HIV (PLWH). Forty PLWH (20 men and 20 women) were randomized into RT+AT group (n = 20; age = 38.3 ± 4.9) or non‐exercise control group (n = 20; age = 37.9 ± 5.1). The RT+AT group was required to perform a nonlinear periodized resistance training program targeting large muscle groups followed by 20 min aerobic exercise at 65‐80% of maximal heart rate. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 43 publications
(52 reference statements)
0
24
1
Order By: Relevance
“…High impact physical activity is thought to be osteogenic, and has been associated with improved bone density at the hip in healthy adolescents. 24 In 2021, a small randomised trial in young adults living with HIV suggested that a combination of resistance and aerobic exercise might improve bone mass; 27 whether the same is applicable for children with HIV remains to be confirmed. In 2019, the first small randomised controlled trial of the oral bisphosphonate, alendronate, given to children with HIV, showed some evidence of improved bone density over 48 weeks of treatment; 28 however, longer term effects on PBM, fracture risk, and rare side-effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…High impact physical activity is thought to be osteogenic, and has been associated with improved bone density at the hip in healthy adolescents. 24 In 2021, a small randomised trial in young adults living with HIV suggested that a combination of resistance and aerobic exercise might improve bone mass; 27 whether the same is applicable for children with HIV remains to be confirmed. In 2019, the first small randomised controlled trial of the oral bisphosphonate, alendronate, given to children with HIV, showed some evidence of improved bone density over 48 weeks of treatment; 28 however, longer term effects on PBM, fracture risk, and rare side-effects are unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, we used Doi plots and the Luis Furuya-Kanamori index (LFK index) [31] to check asymmetry. Finally, we applied influence analyses excluding two "critical" studies [11,14] from the analysis for BMD-LS and FN. A p-value < 0.05 was considered as the significance level for all tests.…”
Section: Discussionmentioning
confidence: 99%
“…In total, our search identified twelve studies [11][12][13][14][15][16][17][18][19][20][21][22] (Figure 1) with 16 exercise and control groups: 362). Table 1 presents the study and participant characteristics of the eligible studies that determined the effect of exercise on bone mineral density among men.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…High impact physical activity is thought to be osteogenic, and has been associated with improved bone density at the hip in healthy adolescents. 24 In 2021, a small randomised trial in young adults living with HIV suggested that a combination of resistance and aerobic exercise might improve bone mass; 27 whether the same is applicable for children with HIV remains to be confirmed. In 2019, the first small randomised controlled trial of the oral bisphosphonate, alendronate, given to children with HIV, showed some evidence of improved bone density over 48 weeks of treatment; 28 however, longer term effects on PBM, fracture risk, and rare side-effects are unknown.…”
Section: Discussionmentioning
confidence: 99%